(untitled) (European Journal of Economics, Finance and Business Development, 2026)
This article examines modern methods of enterprise management in the context of the digital economy and analyzes their role in improving organizational performance. The rapid development of digitalization has increased the importance of utilizing information and communication technologies, automating business processes, and implementing data-driven management systems in enterprise operations. The study highlights the advantages and practical application of contemporary management approaches such as Agile, Lean Management, Enterprise Resource Planning (ERP), and Customer Relationship Management (CRM) systems. Furthermore, the impact of emerging technologies, including Artificial Intelligence (AI), Big Data, cloud computing, and the Internet of Things (IoT), on enterprise management is investigated. The findings indicate that integrating digital technologies into management processes contributes to cost reduction, increased labor productivity, efficient resource utilization, and enhanced enterprise competitiveness. The article also presents scientific conclusions and practical recommendations regarding the organizational, technological, and human resource factors required for successful digital transformation.